FC 122BONE DENSITOMETRY IN RENAL TRANSPLANTED PATIENTS. (29th May 2021) - Ferreira, Ana Carina; Mendes, Marco; Silva, Cecília; Cotovio, Patrícia; Aires, Inês; Navarro, David; Caeiro, Fernando; Salvador, Rute; Correia, Bruna; Cabral, Guadalupe; Nolasco, Fernando; Ferreira, Manuel Anibal A
Abstract: Background and Aims: Renal transplant and associated immunosuppression can influence bone volume. The aim of this study was to analyze the relations between bone biopsy data and levels of bone-related molecules [phosphorus (Pi), Calcium (Ca), Magnesium (Mg), parathyroid hormone (PTH), bone alkaline phosphatase (bAP), calcitonin, vitamin D (vitD), alpha-klotho, fibroblast grow factor (FGF) 23, sclerostin], obtained 1-year after transplantation with bone densitometry findings in the same time point in renal transplanted patients. Method: We performed a prospective cohort study of a consecutive sample of de novo single renal transplanted patients in our unit. At inclusion, demographic, clinical and transplant-related data were collected, X-ray of the pelvis and hands (Adragão score) and echocardiographic findings were recorded. All patients were submitted to a laboratorial evaluation and a bone biopsy at baseline. Patients were followed for 12 months, after which performed laboratorial evaluation, 2nd bone biopsy, echocardiogram, X-ray of pelvis and hands, bone densitometry (DXA) and non-contrast cardiac CT. For this report we use the information of the 2nd analysis: laboratorial information, bone histology information, as well the densitometry evaluation. Continuous variables were presented as medians and categorical variables as frequencies. Associations between variables were performed using Wilcoxon rank-sum test, Fisher exact test, Kruskal Wallis rank test or Spearman correlation test. Multivariate analysis was performed using linear regression models. STATA software was used and p < 0.05 was considered statistically significant. Results: We recruited 84 patients and, at the end of 12 months, we performed a 2nd evaluation in 69 patients. Median age 53 years, 48 men, 53 caucasian (78.8%), median BMI 24.6, median dialysis vintage 55 months. Patients had a median cumulative steroid dose of 5692.5 mg. Analyzing bone biopsies, we found that 28 patients had adynamic bone disease; 6 had hyperparathyroid bone disease; 2 had osteomalacia and 3 other abnormal mineralization; 8 patients presented only with osteoporosis. There was no significant difference between bone volume / total volume pre transplant (18%) and 1 year after transplantation (19%). Using DXA technique, 14 patients were classified has having osteoporosis, and all those had low volume at the bone biopsy. Nevertheless, in 4 patients low bone turnover was also present. The positive predictive value dropped from 100% to 57%, if we add the other abnormalities of bone, in addiction to the volume. DXA exam wasn't a good tool to detect a normal bone volume, as the negative predicted value dropped from 78% (normal volume, irrespective of turnover and mineralization) to 37% (normal bone biopsy). Nevertheless, overall bone volume assessed by a bone biopsy correlated well with densitometry findings. Conclusion: DXA exam isn't a good tool to identify the bone quality. Nevertheless, once osteoporosis is detected the probability of the patient having low bone volume is high, but we still need a bone biopsy in order to exclude mineralization or turnover deviations.